Rancang bangun sistem monitoring dan controlling penyiraman tanaman kangkung berbasis internet of things - Rabbika, Anes Inda; Nugraha, MH; Rohman, Abd; Widyantoro, Widyantoro; Kostaman, Tata; Fauzi, Willy Muhammad; Mustofa, Asep; Widagdo, Tri Jaya (Universitas Muhammadiyah Jakarta, 2023)
The high market demand for water spinach can be a great opportunity to improve the local community's economy. The distribution of water to the kale plants must be done regularly and evenly, while the watering activities of the kale plants by the farmers are still done manually by carrying 20 liters of water. The problem so far is that the farmers water the kale plants by repeatedly carrying water on their backs. so it is necessary to have a control and monitoring system to make it easier for farmers to water the water spinach plants using an internet of thngs system to open and close with sensors that are sent to the database and then displayed in the form of tables and graphs. The results show that the control and monitoring of water sprinkling was successful according to the programmed water discharge.